2005
DOI: 10.21273/hortsci.40.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Location of Endophytic Bacteria in Garden and Wild Strawberry

Abstract: The occurrence of bacteria in different tissues was studied using field-grown strawberries, in vitro-grown strawberries, wild strawberries, and aseptically germinated strawberry seedlings. Strawberry has a number of endophytic bacteria in its the internal tissue, most of which appear to be nonpathogenic. In the in vitro-grown strawberries, all identified isolates were in the genus Pantoea. In field-grown garden and wild strawberries the most common genera were Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Pantoea spp. formed the most frequently isolated papaya endophyte as observed with citrus (Araújo et al 2002) and strawberry (Kukkurainen et al 2005). Pantoea has been isolated from other plant sources like grapevine (Bell et al 1995), rice (Feng et al 2006), and banana (P. Thomas, unpublished results).…”
Section: Discussionmentioning
confidence: 97%
“…Pantoea spp. formed the most frequently isolated papaya endophyte as observed with citrus (Araújo et al 2002) and strawberry (Kukkurainen et al 2005). Pantoea has been isolated from other plant sources like grapevine (Bell et al 1995), rice (Feng et al 2006), and banana (P. Thomas, unpublished results).…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies report the presence of seed microorganisms but few have examined their presence of these microbes post germination (Mundt & Hinkle, ; Cankar et al ., ; Kukkurainen et al ., ; López‐López et al ., ). In this study, pyrosequencing of 16s rRNA gene amplicons was used to examine the bacterial communities of spinach seeds and aerial tissues of spinach after germination (cotyledons) and plants (3–4 leaf stage).…”
Section: Discussionmentioning
confidence: 99%
“…The seed coat, embryo and endosperm of diverse crops such as alfalfa (Charkowski et al ., ), Norway spruce ( Picea abies L. H. Karst) (Cankar et al ., ), cereals and cucurbits (Mundt & Hinkle, ) yield culturable bacteria. Vertical transmission of bacteria from seed to germinated seedlings is reported in various species of Eucalyptus (Ferreira et al ., ), strawberry ( Fragaria × ananassa Duchesne) (Kukkurainen et al ., ), beans (López‐López et al ., ), rice (Cottyn et al ., ), Norway spruce (Cankar et al ., ) and tomato ( Lycopersicon esculentum L.) (Guo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that bacterial endophytes are common in plant tissues grown in vitro and that their beneficial effects on plant growth indicate that they may be useful as growth-promoting agents. In previous studies, a succession of bacterial communities that colonized pineapple microplant organs in vitro were characterized ( Abreu-Tarazi et al, 2010 ) Similarly, endophytic bacteria were isolated from strawberry tissues cultivated in vitro ( Kukkurainen et al, 2005 ; Dias et al, 2009 ), and their beneficial effect on the acclimatization of the seedlings under greenhouse conditions was demonstrated ( Dias et al, 2009 ). Recently, the effects of bacterial endophytes in different in vitro culture phases and in different plant organs of Prunus avium were studied; isolates of the endophytes Rhodopseudomonas palustris and Microbacterium testaceum promoted rooting in two difficult-to-propagate genotypes ( Quambusch et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%